Transition life cycle assessment: A new method to face ecological transition - Ventura, Anne (Frontiers in Sustainability, 2022)
Transition can be defined as deep-structural changes in interrelated economic sectors. Climate change issue calls for a transition in which all actors can be involved and where the aim is the global interest rather than individual ones. LCA should be used to assess the environmental impacts of transition solutions, however, existing LCAs are not adapted mainly because they are conducted at product-level and rely upon economic assumptions that are unsuitable for a transition context. A new type of LCA, called transition LCA is conceptually described. It aims at studying transition scenarios in a geographical context, and that can be relied to various technological paths. Differences with existing LCAs is that several functional units can be included, and that results concern the changes of the system itself rather than the individual impacts of products. Transition LCA is also related to a specific geographical context in order to account for existing limits of resources and especially constraint resources such as waste, and to account for the match of flows between production and demand which determines the size of the geographical area. This type of modelling can be reached by coupling LCA with MFA at the suitable geographical scale. Transition LCA also requires specific interpretation steps dedicated to the identification of preferable scenarios and action levers hold by each involved actor. This interpretation requires integrating actors’ identification and their decision models as mechanisms inside the system model. It also requires additional methods to generate all actions possibilities and to conduct suitable sensitivity analysis. This method has presently been applied by parts but not as a whole and not as a single numerical tool. These parts are currently being developed in a single computing Python language, in order to become compatible with Brightway 2.